Effects of Cholinergic Enhancing Drugs on Cholinergic Transporters in the Brain and Peripheral Blood Lymphocytes of Spontaneously Hypertensive Rats - Tomassoni, Daniele; Catalani, Assia; Cinque, Carlo; Antonietta Di Tullio, Maria; Khosrow Tayebati, Seyed; Cadoni, Angela; Ejike Nwankwo, Innocent; Traini, Enea; Amenta, Francesco (Current Alzheimer Research, 2012)
Cholinergic hypofunction is a trait of Alzheimer's disease and vascular dementia and countering it is one of the main therapeutic strategies available for these disorders. Cholinergic transporters control cellular mechanisms of acetylcholine (ACh) synthesis and release at presynaptic terminals. This study has assessed the influence of 4 week treatment with two different cholinergic enhancing drugs, the cholinergic precursor choline alphoscerate (alpha-glyceryl-phosphorylcholine) or the acetylcholinesterase (AChE) inhibitor galantamine on high affinity choline uptake transporter (CHT) and vesicular ACh transporter (VAChT) expression in the brain of spontaneously hypertensive rats (SHR). SHR represent an animal model of cerebrovascular injury characterized by cholinergic hypofunction. Analysis was performed by immunochemistry, ELISA and immunohistochemistry on frontal cortex, striatum and hippocampus. Immunochemical and ELISA analysis was extended to peripheral blood lymphocytes (PBL), used as a peripheral reference of changes of brain cholinergic markers. An increased expression of VAChT and CHT was observed in brain areas investigated and in PBL of SHR. The similar trend for cholinergic transporters observed in brain and PBL suggests these cells may represent a marker of brain cholinergic transporters. Treatment with choline alphoscerate increased CHT and to a greater extent VAChT expression. Treatment with galantamine countered the increase of CHT and VAChT. The different activity of the cholinergic precursor and of the AChE inhibitor on parameters investigated is likely related to their mechanism of action. Choline alphoscerate increases ACh synthesis and release. This requires an augmentation of systems regulating neurotransmitter uptake and storage. The effect of choline alphoscerate on CHT and VAChT observed in this study suggests an improved synaptic efficiency elicited by the compound. The AChE inhibitor slows-down ACh degradation in the synaptic cleft. A greater availability of neurotransmitter elicited by galantamine counters the enhanced activity of cholinergic transporters compensating cholinergic deficits. Differences in the activity of the cholinergic precursor and AChE inhibitor investigated on CHT and VAChT suggests that association between choline alphoscerate and AChE/cholinesterase inhibitors may represent a strategy for potentiating deficient cholinergic neurotransmission worthwhile of being investigated in clinical trials.
Keywords: dementia disorders